Faculty Readiness in Education in the New Normal: Basis ForIntervention Program (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic has caused significant disruptions in the education sector worldwide with most institutions opting to close physical classrooms and shift to remote learning to mitigate the spread of the virus. This study aimed to determine the faculty readiness in education in the new normal of Guimaras State College, Mclain, Buenavista, Guimaras, Philippines on School Year 2020-2021 as a basis for the development of an intervention program. The study used a quantitative research design, and the respondents were the 107 faculty members selected through purposive sampling. The results showed that the overall level of faculty readiness was high with no significant differences observed when classified according to age, sex, educational attainment, and years in teaching service. The study recommends the implementation of an intervention program to further improve faculty readiness and address concerns related to the shift to remote learning.